Placebo Responses and Their Clinical Implications in Fibromyalgia: A Meta-Analysis Using SSRI and SNRI Trials - Koechlin, Helen; Kharko, Anna; Probst, Tamara; Pradela, Julia; Buechi, Stefan; Locher, Cosima (Frontiers in Pain Research, 2021)
Background. Fibromyalgia (FM) is a chronic primary pain condition, associated with widespread musculoskeletal pain, disturbed sleep, fatigue, cognitive dysfunction, and a range of comorbid conditions such as irritable bowel syndrome, and depression. Despite its high prevalence of 2% in the general population, FM continues to pose scientific and clinical challenges in definition, aetiology, and day-to-day management. In terms of treatment, FM can be treated with selective serotonin reuptake inhibitors (SSRIs), serotonin-norepinephrine reuptake inhibitors (SNRIs). Objective. Patients with FM and other chronic primary pain syndromes are known to experience substantial and clinically relevant placebo effects. An update of the placebo responses for various outcomes in the FM population and especially a discussion about clinical implications is therefore needed. Methods. We used data from a large data pool that includes randomized controlled trials (RCTs) examining within-placebo mean change scores of baseline vs follow-up assessments in FM trials of SSRIs and SNRIs. The primary outcomes were pain, functional disability, and depression and using different scales. We assessed heterogeneity of included trials. Results. A total of 29 RCTs with N = 8453 patients suffering from FM were included in our analysis. Within-placebo mean change scores of baseline vs follow-up assessments were large for pain (mean change = 2.31, 95% CI: 0.42 to 4.21, p = .017), functional disability (mean change = 3.31, 95% CI: 2.37 to 4.26, p < .000), and depression (mean change = 1.55, 95% CI: 0.92 to 2.18, p < .000). Heterogeneity was found to be large for all outcomes. Impact. Our results provide preliminary evidence that placebo responses, which also consist of nonspecific effects, might play a role in the treatment of FM. Furthermore, we highlight limitations of our analyses and make suggestions for future studies.